Rethinking the discovery of early music + Living differently with known early music - Forment, Bruno 1978-; COST Action 21161 – EarlyMuse Universytet Wrocławski 22-26 May 2024 (Brussels COST, 2023)
Discussions held at the REMA Summit in Bruges last December highlighted the growing role of research in the early music ecosystem, accompanied by an increasing demand for complementary skills. These skills range from exploring new avenues in musicological and artistic research to mastering dramaturgy, organization, copywriting, and audiovisual and digital technologies to effectively communicate the results of historically informed performance. While the concept of ‘storytelling’ to convey the full narrative of early music from score to performance is undoubtedly a positive strategy for bridging research with performance and audience engagement, it requires substantial (often unpaid) effort.Nevertheless, examples demonstrate that researchers and performers of early music have significantly enhanced their efficiency and adeptly embraced the role of ‘storytellers.’ Moreover, technological advancements have made storytelling tools more affordable and user-friendly. During our meeting, we aim to gather and discuss a selection of best practices and derive broader recommendations from them for our report.
FRIS
Editorial review
Keywords: Resounding Libraries: Unfolding Archived Knowledge Through Artistic Research; Early music